2022
DOI: 10.3390/nu14030545
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Polyphenols on Vascular Health and Hypertension: Current Evidence and Mechanisms of Action

Abstract: The aim of this review was to explore existing evidence from studies conducted on humans and summarize the mechanisms of action of dietary polyphenols on vascular health, blood pressure and hypertension. There is evidence that some polyphenol-rich foods, including berry fruits rich in anthocyanins, cocoa and green tea rich in flavan-3-ols, almonds and pistachios rich in hydroxycinnamic acids, and soy products rich in isoflavones, are able to improve blood pressure levels. A variety of mechanisms can elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 116 publications
1
44
0
1
Order By: Relevance
“…A large body of evidence supports the intake of natural nutrients such as polyphenols [ 32 ] and antioxidant vitamins [ 33 ], as well as dietary patterns such as the Mediterranean diet [ 34 ], Dietary Approaches to Stop Hypertension [ 35 ], the Nordic Diet [ 36 ], and Traditional Asian Diets [ 37 , 38 , 39 ], can prevent CVDs. The findings of three large prospective cohorts with up to 32 years of follow-up showed that greater adherence to various healthy eating patterns was associated with a lower risk of CVD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence supports the intake of natural nutrients such as polyphenols [ 32 ] and antioxidant vitamins [ 33 ], as well as dietary patterns such as the Mediterranean diet [ 34 ], Dietary Approaches to Stop Hypertension [ 35 ], the Nordic Diet [ 36 ], and Traditional Asian Diets [ 37 , 38 , 39 ], can prevent CVDs. The findings of three large prospective cohorts with up to 32 years of follow-up showed that greater adherence to various healthy eating patterns was associated with a lower risk of CVD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within berries, there are three classes of polyphenols in particular that may account for a beneficial effect on BP: anthocyanins, condensed tannins and ellagic acid [8].…”
Section: Berry Polyphenols and Blood Pressurementioning
confidence: 99%
“…However, while this nutritional profile is common to most fruits and vegetables, the specific effect proposed for berries on BP must involve further features, acting in addition or synergistically to the above mentioned ones. What is distinctive to berries is the presence of a number of phytochemicals within the family of polyphenols [8].…”
Section: Introductionmentioning
confidence: 99%
“…Flavanone hesperetin, in combination with sodium cyclic lysophosphatidic acid, showed significant antiaging effects on skin hydration and elasticity in a single-center clinical trial [ 23 ]. In general, data from several studies suggest that higher dietary intake of flavonoids may be associated with better cognitive health [ 24 , 25 ], improved prognosis for cardiovascular diseases [ 26 , 27 ], and decreased body weight [ 28 ]. Taken together, due to antioxidant activity, selective affinity to several biological targets, and high safety profiles, flavonoids are a prospective class of natural compounds for drug development [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%